2021
DOI: 10.18502/jri.v22i2.5804
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Consequences and Vertical Transmission Potential of SARS- CoV-2 Infection: Seeking Answers From a Preliminary Observation

Abstract: The article's abstract is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 16 publications
(14 reference statements)
3
12
0
Order By: Relevance
“…In this study, 10.8% of women presented with leaking per vagina. Similar findings were also reported by Kalpana et al [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, 10.8% of women presented with leaking per vagina. Similar findings were also reported by Kalpana et al [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Increased incidence of caesarean delivery (70.3%) was observed in COVID-19 positive pregnant women in the present study. High caesarean rates in COVID-19 infected pregnant women were also observed in some other studies [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Therefore, it is reasonable to speculate that the proinflammatory state of SARS-CoV-2 infection during pregnancy may precipitate negative consequences in children [ 13 , 14 ]. In addition to potential risk of vertical transmission, SARS-CoV-2 may indirectly lead to adverse perinatal and longer-term neurodevelopmental outcomes [ 15 , 16 ]. The inner ear is a complex structure which starts to develop early during pregnancy (Carnegie stages 14–16) and progresses during early gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Out of them, 28 records were included for full-text review , and 14 records were excluded (three due to non-inclusion of the study population, five due to small neonatal sample size, two due to not reported outcomes of interest, one due to reporting on unique maternal population, one due to non-confirmation of maternal SARS-CoV-2 positivity, and two due to repetition of data). Finally, 14 Indian studies were included in this meta-analysis; a total of 3,542 SARS-CoV-2 infected pregnant women and 3,551 delivered neonates were found eligible (see Figure 1 and Table 2) [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. As Figure 3 indicates, the pooled prevalence of prematurity was 18.89% (…”
Section: Resultsmentioning
confidence: 99%